Fault lines in China's economic terrain - Wolf, Charles, Jr., 1924-2016 (RAND, 2003)
What are the major challenges, fault lines, and potential adversities (these terms are used synonymously), that China's economic development will encounter over the next decade? How severely will China's overall economic performance be affected if these adversities occur separately or in clusters? This book addresses these key questions. China has confronted in the past two decades five of the eight fault lines that the authors consider (unemployment, corruption, water resources, HIV/AIDS, and financial fragility), and, nonetheless, it has sustained high rates of economic growth. Therefore, in assessing the potential effects of these fault lines on China's future economic performance, the authors focus on whether, why, and by how much their intensities may increase--that is, on changes, rather than on the prevailing levels of each fault line. For the other three fault lines examined, which have not previously occurred or recurred--oil price shocks, foreign-direct-investment shrinkage, and serious military conflicts--the authors consider the circumstances under which they might arise and their resulting economic effects. For each of the eight fault lines, the authors estimate a "bottom-line" in terms of expected effects on China's annual growth rate over the next decade, drawing on a variety of methods, models, and judgments to make these estimates. The authors suggest that the probability that none of these individual setbacks will occur is low, while the probability that all will occur is still lower. Because of interdependencies among the fault lines, it is highly likely that several separate adversities will cluster if any one of them occurs. For examples: an internal financial crisis would have serious negative effects on the relative attractiveness of foreign investment in China, contributing to shrinkage of foreign direct investment; epidemic disease would intensify water pollution problems and would discourage foreign investment